2007
DOI: 10.1614/wt-06-099.1
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Herbicides on ‘zenith’ Zoysiagrass Seedlings

Abstract: Improved cultivars of zoysiagrass established by seed are now available, but little is known about the safety of herbicides on zoysiagrass seedlings. Our objective was to determine the turf safety of various herbicides when applied from emergence to 4 wk after emergence (WAE) of ‘Zenith’ zoysiagrass. Oxadiazon (3.4 kg ai/ha), MSMA (2.3 kg ai/ha), and pronamide (1.1 kg ai/ha) did not reduce coverage 7 WAE when applied at emergence or later and caused only temporary discoloration of seedlings. Foramsulfuron (0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 14 publications
3
19
0
Order By: Relevance
“…Injury from combination products was greater in 2007 than 2008 on seedling turf, and in general these products caused more injury on seedlings than reports on established turf (5,7,10,30). This is consistent with previous reports in bermudagrass and zoysiagrass, where herbicide tolerance of seedlings improves as they mature (19,21).…”
Section: Herbicide Injury On Seedling Sea Spray Seashore Paspalumsupporting
confidence: 93%
“…Injury from combination products was greater in 2007 than 2008 on seedling turf, and in general these products caused more injury on seedlings than reports on established turf (5,7,10,30). This is consistent with previous reports in bermudagrass and zoysiagrass, where herbicide tolerance of seedlings improves as they mature (19,21).…”
Section: Herbicide Injury On Seedling Sea Spray Seashore Paspalumsupporting
confidence: 93%
“…Fenoxaprop is registered for goosegrass ( Eleusine indica L.) control in zoysiagrass (10); however, Patton and Reicher (11) reported that fenoxaprop applied to Zenith zoysiagrass injured seedlings and reduced ground cover. Weed pressure can be significant in stands of the slow growing zoysiagrass (9,10,11,12). Selecting the appropriate herbicide will speed establishment (10), but herbicides used to reduce weed competition could also impede zoysiagrass growth and be more harmful than helpful (12).…”
Section: Bearded Sprangletop Control and Turfgrass Injury As Influencmentioning
confidence: 99%
“…Pronamide provides selective postemergence control of annual bluegrass and perennial ryegrass without causing damage or growth reduction to Zenith zoysiagrass seedlings (30). This product is registered as a restricted use pesticide which could preclude its use on some golf courses.…”
Section: Post‐seeding Weed Controlmentioning
confidence: 99%
“…Herbicides such as metsulfuron (2‐[[[[(4‐methoxy‐6‐methyl‐1,3,5‐triazin‐2‐yl)amino]carbonyl]amino]sulfonyl]benzoic acid) and fenoxaprop ((±)‐2‐[4‐[(6‐chloro‐2‐benzoxazolyl)oxy]phenoxy]propanoic acid) cause significant reduction in Zenith zoysiagrass coverage when applied to seedlings and should not be used during establishment (Figs. 8 and 9) (30,34). Other herbicides such as fluazifop ((R)‐2‐[4‐[[5‐(trifluoromethyl)‐2‐pyridinyl]oxy]phenoxy]propanoic acid) and foramsulfuron can damage Zenith zoysiagrass seedlings (30,34) and thus should be used on seedlings only when absolutely necessary and no other weed control options are available (Fig.…”
Section: Post‐seeding Weed Controlmentioning
confidence: 99%
See 1 more Smart Citation